Collaborative Pemerintah Desa Sekongkang Bawah dan PT. AMMAN MINERAL NUSA TENGGARA dalam Pengelolaan Corporate Sosial Responsibility Guna Peningkatan Pendidikan dan Kesehatan Masyarakat - Febriansyah, Krisna; Hidayat, Rahmad; Rifaid, Rifaid (Indonesian Journal Publisher, 2024)
The collaboration between the Sekongkang Bawah Village Government and PT Amman Mineral Nusa Tenggara (AMNT) in managing Corporate Social Responsibility (CSR) has had a significant impact on the education and health of the community. Amid the recent declaration on Early Childhood Care and Education in Southeast Asia, AMNT has been actively involved in developing human resources through various initiatives, including the rehabilitation of Early Childhood Education (PAUD) and the improvement of access to clean water to reduce stunting in West Sumbawa Regency. Through the Employee Participation Program (EPP), AMNT involves employees, business partners, and local communities in this effort. This research aims to evaluate and understand the collaboration between the village government and PT. AMNT in managing CSR with a focus on improving education and public health in Sekongkang Bawah Village. The research method used includes a descriptive qualitative approach, with data collection techniques such as interviews, observations, and documentation, as well as interactive analysis to obtain a holistic understanding. The results of this study indicate that collaborative governance in the management of Corporate Social Responsibility includes: 1) Network Structure, The collaboration between the Sekongkang Village Government and PT AMNT in the CSR program has successfully improved the quality of education and health in Sekongkang Bawah Village through programs such as scholarships, mechanic courses, and football development. This shows their commitment to community development. The synergy between PT AMNT and the Village Government in a strategic partnership has effectively improved community welfare through a coordinated approach and good monitoring. 2). Commitment to a Common Purpose, PT AMNT actively plays a role in improving community welfare through education and health initiatives, such as providing scholarships and establishing health posts. A good understanding between PT AMNT and the Sekongkang Bawah Village Government has supported the implementation of integrated and sustainable development programs. 3). Akses ke Sumber Daya, The integration of local human resources by PT AMNT has improved education and health services, as well as provided job opportunities and skill development for the local population. PT AMNT's commitment to allocating financial resources such as scholarships and educational equipment has provided significant benefits to the community. PT AMNT's efforts in building and improving educational and health infrastructure have a sustainable positive impact on the Sekongkang Bawah community.